Circulation of hepatitis B virus genotype-E among outpatients in tertiary hospitals in the Niger-Delta region of Nigeria (2022)
Introduction: Hepatitis B virus (HBV) infection continues to be a significant public health challenge globally, with higher disease burden in developing countries. HBV genotypes are associated with different geographical regions and clinical outcomes. Limited information exists on epidemiology of HBV in the Niger-Delta region (South-South) of Nigeria. Consequently, this study was designed to characterise hepatitis B virus infection among outpatients in selected tertiary hospitals in the region. Methodology: Between June and August 2017, consenting nine hundred asymptomatic out-patients were enrolled and initially screened for HBV infection using one step Hepatitis B surface antigen (HBsAg) strip and subsequently re-tested using HBsAg and Hepatitis B core total antibody (anti-HBc) specific Enzyme-Linked Immunosorbent Assay (ELISA). Blood serum with detectable HBsAg were subsequently subjected to DNA extraction, S-gene amplification using a nested polymerase chain reaction (PCR) protocol, gel electrophoresis, sequencing and phylogenetic analysis. Results: Seroprevalence of HBsAg was 4.6% (95% CI 2.5-7.1) and anti-HBc was 10.1% (95% confidence interval (CI) 6.1-15.3). Of the 41 HBsAg positive samples subjected to DNA extraction and HBV S-gene specific PCR, only 6 (14.6%) yielded the expected ~408bp band. Phylogenetic analysis based on HBV pre-S/S sequences identified all six typable samples as genotype E, subtype ayw4 of the West African clade. Conclusion: Results of the study confirm the presence and circulation of HBV genotype-E in the Niger-Delta region of Nigeria, thus corroborating the inclusion of the country in the Genotype E crescent. The authors advocate value-added HBV intervention in the region and the country at large.